Muscle ribosomal protein synthesis in normal pregnancy: implication for carrier detection in Duchenne muscular dystrophy. Issue 2 (June 1974) - Ionasescu, Victor; White, Charles; Zellweger, Hans; Lewis, Ruth; Conway, Thomas W.
Abstract : Muscle samples of rectus abdominis were obtained from 11 normal pregnant women 21-30 years old during elective Caesarean section and from 10 normal, non-pregnant controls of comparable age. The in-vitro amino-acid incorporation of polyribosomes extracted from the muscle homogenates of the pregnant women showed high activity for the synthesis of non-collagen protein in six cases, while control values were found in five cases. These results indicate that carrier detection in Duchenne muscular dystrophy based on increased muscle ribosomal protein synthesis cannot be done accurately during pregnancy, unless adequate values for known carriers at a comparable stage of gestation are available.